0991 Improvements in Insomnia and Subjectively Unrefreshing Sleep following Sleep Hygiene Intervention. (12th April 2019) - Groenewold, Naeva; Mason, Timothy; Williams, Michelle; Kavanaugh, Colin; Wang, Huaping; Rhode, Sophia; Zallek, Sarah N
Abstract: Introduction: Poor sleep is associated with a variety of health and non-health outcomes, including increased risk of obesity, cardiovascular disease, type II diabetes, impaired immune function, mood disorders, increased missed work, and decreased workplace productivity. One study found that people later diagnosed with insomnia incurred a direct medical cost $924 higher per six-month period than people not later diagnosed with insomnia. The effectiveness of sleep hygiene education on sleep outcomes seems to be in debate. Many studies find some effect of sleep hygiene on sleep habits, though perhaps not as much as other sleep-related interventions. To our knowledge, none have yet evaluated the effects of an informational video on sleep habits and outcomes. The aim of this study was to assess the effectiveness on a brief video intervention on sleep-related outcomes. Methods: A sample of OSF HealthCare Saint Francis Medical Center employees (n = 573, age 18 - 69) completed a 20-question survey about perceived sleep quality and workplace outcomes. The participants were randomly assigned to intervention (n = 271) and control groups (n = 302), which completed either a sleep hygiene video or a wellness sham presentation, respectively. Participants completed a post-intervention survey two weeks later. Univariate and multivariate analyses were performed. Results: The proportion of intervention subjects who reported frequent insomnia decreased from 43.17% to 33.21% following the intervention, which was a significantly larger change than the 38.41% to 37.09% decrease expressed by the sham-control group (p = 0.0134). Intervention subjects also reported a significant decline in unrefreshing sleep, with 61.25% noting unrefreshing sleep pre-intervention, and only 49.82% reporting unrefreshing sleep post-intervention. This improvement was significantly larger than the change of 52.65% to 52.32% in the sham-control group (p = 0.0021). Conclusion: These findings that insomnia and unrefreshing sleep are improved 2 weeks following viewing of a sleep hygiene intervention compared with a control group, indicate that this could be a useful tool to teach proper sleep hygiene. Our next steps will be to evaluate if there were concomitant changes in workplace outcomes. Support (If Any): N/A